Principles of interpretation of collective agreements within the meaning of Art. 9 of the Labor Code and other labor law agreements - Pieczonka, Piotr (Studia Iuridica Toruniensia, 2023)
The article focuses on the analysis of the ways of interpreting the provisions of collective agreements within the meaning of Art. 9 of the Labor Code, i.e. agreements of a normative nature and on the basis of interpretation of obligatory agreements. The starting point for considering how to interpret this type of collective agreement is to present the differences between both types of agreements and the impact of the legal nature of the agreement on the methods of interpreting its provisions.